The Effects Of Gamification And Lyrical Music On Reading Comprehension Of Esl Students At Mahabodhi Vidya High School - Margareta Ajeng Kusumastuti; Lusiana Idawati (Journal on Education, 2025)
This research explores the challenges faced by ESL students in reading comprehension, specifically focusing on Grade 12 students at Mahabodhi Vidya High School. Unit test results indicate that reading comprehension scores are significantly lower than those for listening, grammar, and vocabulary, largely due to difficulties with unfamiliar vocabulary and inconsistent application of reading strategies. To address these challenges, the study employs a quasi-experimental design with non-equivalent groups to examine the impact of gamification and lyrical music on vocabulary acquisition and comprehension of informational texts. Two experimental groups (one using gamification and the other using lyrical music) and a control group participated in pretests and posttests aligned with the Common Core State Standards. Statistical analyses, including paired t-tests, one-way ANOVA, and N-Gain calculations, demonstrated that while both interventions improved reading comprehension, gamification had a significantly stronger effect, as evidenced by higher mean scores in the gamification group compared to the lyrical music group. The interactive features of gamification, such as real-time feedback and competitive elements, fostered deeper engagement, whereas lyrical music facilitated learning through emotional connections. Grounded in the Active View of Reading theory, this study highlights how these strategies address multiple reading processes and enhance student motivation. Although both approaches proved beneficial, gamification exhibited greater potential, offering valuable insights for innovative instructional methods to enhance ESL students’ reading comprehension.